Principal's Policy on Limited Face-to-Face Learning During the COVID-19 Pandemic - Hafidhudin, Didin; Azlansyah, Azlansyah (research, training and philanthropy institution Natural Aceh, 2024)
The research conducted at MIS Al-Ikhwah Pontiana aimed to analyze the implementation of Face-to-Face Learning (PTM) policies during the COVID-19 pandemic. The study involved principals, students, teachers, and parents of students. Data collection techniques included interviews, observation, and documentation. The results showed that the Principal's Face-to-Face Learning policy followed government guidelines, with teachers checking body temperature, praying, and teaching for one hour before entering the class. However, problems with implementing Face-to-Face Learning included unclear and stuffy children's voices, difficulty concentrating, and technological stuttering among teachers. Teachers had to work extra to summarize lessons and could not know the students. The study also found that the Principal's Policy had practical implications on the quality of learning regarding teaching and learning processes, facilities and infrastructure, and learning outcomes. The results showed that learning outcomes before Face-to-Face Learning increased before implementing the Policy.